How to Contribute to the Progress of Neuroendocrinology: Discovery of GnIH and Progress of GnIH Research - Tsutsui, Kazuyoshi; Ubuka, Takayoshi (Frontiers in Endocrinology, 2018)
It is essential to discover novel neuropeptides that regulate the functions of pituitary, brain and peripheral secretory glands for the progress of neuroendocrinology. Gonadotropin-releasing hormone (GnRH), a hypothalamic neuropeptide stimulating gonadotropin release was isolated and its structure was determined by Schally’s and Guillemin’s groups at the beginning of the 1970s. It was subsequently shown that GnRH is highly conserved among vertebrates. GnRH was assumed the sole hypothalamic neuropeptide that regulates gonadotropin release in vertebrates based on extensive studies of GnRH over the following three decades. However, in 2000, Tsutsui’s group isolated and determined the structure of a novel hypothalamic neuropeptide, which inhibits gonadotropin release, in quail, an avian species, and named it gonadotropin-inhibitory hormone (GnIH). Following studies by Tsutsui’s group demonstrated that GnIH is highly conserved among vertebrates, from humans to agnathans, and acts as a key neuropeptide inhibiting reproduction. Intensive research on GnIH demonstrated that GnIH inhibits gonadotropin synthesis and release by acting on gonadotropes and GnRH neurons via GPR147 in birds and mammals. Fish GnIH also regulates gonadotropin release according to its reproductive condition, indicating the conserved role of GnIH in the regulation of the hypothalamic-pituitary-gonadal (HPG) axis in vertebrates. Therefore, we can now say that GnRH is not the only hypothalamic neuropeptide controlling vertebrate reproduction. In addition, recent studies by Tsutsui’s group demonstrated that GnIH acts in the brain to regulate behaviors, including reproductive behavior. The eighteen years of GnIH research with leading laboratories in the world have significantly advanced our knowledge of the neuroendocrine control mechanism of reproductive physiology and behavior as well as interactions of the HPG, hypothalamic-pituitary-adrenal and hypothalamic-pituitary-thyroid axes. This review describes how GnIH was discovered and GnIH research progressed in this new research era of reproductive neuroendocrinology.